1990
DOI: 10.1115/1.2899289
|View full text |Cite
|
Sign up to set email alerts
|

Improved Methods for the Prediction of Chatter in Turning, Part 1: Determination of Structural Response Parameters

Abstract: The dynamics of the structure of a lathe at the cutting point are directly identified under normal machining operation using an improved version of a method originally proposed by Opitz and Weck. The improved method is based on the interrupted cutting of a specially designed, surface-modulated workpiece that provides a strong, broadband excitation. This interrupted cutting has been theoretically shown to permit the identification of the structure’s dynamics from input-output measurements, despite the intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The value of the damping coefficient K Ã Z 2:01 10 5 N m K2 s was estimated by extrapolating the value given by Wu for steel. An acceptable agreement between the model and the experimental results, see Fig. 14, was obtained by considering an increasing of the damping ratio xZ 0:0769 as it was been indicated in [34,35]. However, it is clear that further research have to be conducted in order to obtain a more acceptable model for ploughing mechanism when the internal damping of the structure is weak.…”
Section: Width Of Cut (Mm)mentioning
confidence: 65%
See 1 more Smart Citation
“…The value of the damping coefficient K Ã Z 2:01 10 5 N m K2 s was estimated by extrapolating the value given by Wu for steel. An acceptable agreement between the model and the experimental results, see Fig. 14, was obtained by considering an increasing of the damping ratio xZ 0:0769 as it was been indicated in [34,35]. However, it is clear that further research have to be conducted in order to obtain a more acceptable model for ploughing mechanism when the internal damping of the structure is weak.…”
Section: Width Of Cut (Mm)mentioning
confidence: 65%
“…Many authors have indicated that the process damping, due to the ploughing mechanism, can induce a significant increase of the internal damping of the structure, Minis et al [34] and Shawky and Elbestawi [35]. For the experimental setup presented in Section 1, the internal damping of the structure is weak (ðxZ c=ð2 ffiffiffiffiffiffi km p ÞZ 0:00513Þ).…”
Section: Width Of Cut (Mm)mentioning
confidence: 97%
“…In this paper, the machining process is considered from the perspective of complex interrelated dynamics of the machine tool mechanical structure and workpiece-cutting interactions. This approach was initially proposed by Merritt [14], Kegg [15], Minis et al [16][17][18] and Tlusty and Moriwaki [19], and was extended by Bordatchev and Orban [20] to deal with the dynamics of the machine tool spindle only. The concepts are expanded upon in this paper to include the dynamics of the cutting tool and thus create a more complete dynamic model of this important machine tool subsystem.…”
Section: Basics Of Machining Process Dynamicsmentioning
confidence: 99%
“…The reason for this problem is that the cutting force which excites the machine tool is periodic and if it can fulfill the assumption of white noise excitation, this problem will not exist. To solve this problem, based on the research by Minis [8], we [9] presented a random cutting technique to produce white noise excitation by interrupted cutting of a specially designed workpiece, of which the surface is modulated with pseudorandomly distributed teeth and channels. With this random exciting technique, we propose a complete methodology for applying OMA in the case of heavy machine tool to estimate the dynamic modal parameters of the whole structure during machining.…”
Section: Introductionmentioning
confidence: 99%